What Makes Firms Leave the Neighbourhood?. (June 2014) - Weterings, Anet
Limited attention has been paid to neighbourhood conditions as a driver of firm relocation choices. Using a panel dataset (1999–2006) of actual firm relocations in the Netherlands, the effect of different neighbourhood conditions on firms' propensity to relocate was estimated. Results show that, besides firm and regional characteristics, neighbourhood conditions also affect firms' relocation choices, but which conditions matter depends on the firm's industrial activity and size. The relocation decision of consumer services in particular is affected by neighbourhood conditions, while the choice of manufacturing, wholesale and business services firms is affected more by increases in population density. Nevertheless, a higher number of shops, cafes and restaurants and a more attractive physical environment do lower the probability that business services leave the neighbourhood, while manufacturing and wholesale firms are more inclined to leave neighbourhoods when a higher share of consumer services is not in use.